The Shocks of Climate Change on Bank Loans - Sugiarto, Agus; Puspani, Ni Nyoman; Trisilia, Mustika Septiyas (International Journal of Energy Economics and Policy, 2023)
Climate change poses new challenges to the banking sector. Thus, in this paper, we investigate the effect of climate change on bank loans using panel data covering 7,865 banks in Indonesia from 2011-2021. We define bank loans into three variables, i.e., outstanding credit, non-performing loans (NPLs), and interest rates. Our results suggest that, of the six climate-related disasters, the flood has a significant and consistent effect. An increase in the frequency of floods reduces credit and increases NPLs. Consistent results are found for disaster risk index scores. The empirical results show that there is a negative effect of climate change on bank loans so further policies from banks and regulators’ side are needed.